Induction of Systemic Resistance by Rhizobacterial and Endophytic Fungi against Foot Rot Disease of Piper nigrum L. by Increasing Enzyme Defense Activity - M.S., Shobha; N., Lakshmi Devi; S., Mahadeva Murthy (International Journal of Environment, Agriculture and Biotechnology, 2019)
Two strains of rhizobacteria, Bacillus subtilis and Pseudomonas fluorescens and two strains of endophytic fungi Trichoderma viride and Trichoderma asperellum were selected as inducers of systemic resistance against Phytophthora capsici and were tested individually for biological control of foot rot disease of pepper. Black pepper vines were grown under greenhouse and challenge inoculated with P. capsici were selected for analyzing the disease index, chitinase, peroxidase, phenylalanine ammonia lyase activity, polyphenol oxidase, β-1, 3-glucanase assay and estimation of phenol content. Treatments with B. subtilis and T. viride isolates provided protection to pepper plant against P. capsici infection as observed with reduced per cent disease incidence showed 20 and 18% as compared to untreated control. Increases in the enzyme level were detected in different strains of pepper vines at time intervals after challenge inoculation. The study reveals the potential of B. subtilis and T. viride as biocontrol agent for prevention of P. capsici infections in black pepper.